Cultural Awareness of Pre-Service EFL Teachers in an Indonesian Higher Education Context - Sahril Nur; Andi Anto Patak; La Sunra (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2022)
Abstract. It is not enough to teach a language without acknowledging culture while teaching English as a Foreign Language, so teachers must be culturally conscious of incorporating culture into their teaching activities. This research was conducted to investigate the cultural awareness of pre-service EFL teachers in the higher education context. The aim is to find out the cultural understanding of cultural differences of the pre-service EFL teachers. This research used a qualitative research design. The participants of this research were 20 pre-service EFL teachers who had attended the PPG program in 2018. A questionnaire by Marx and Moss (2011) on My Cultural Awareness Profile (MyCAP) was adopted as an instrument of this research. The study's findings showed that the participants had a significant cultural awareness and understanding of cultural differences. However, due to the limited time and approach employed in the study, the researchers hope that more researchers will be attracted to look further into intercultural understanding in higher education with different subjects and approaches.Keywords: Cultural Awareness, Cultural Understanding, Cultural Differences, Pre-Service EFL Teacher